2021
DOI: 10.4274/tao.2021.2021-1-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Korean Red Ginseng on Noise-Induced Hearing Loss

Abstract: Objective: Noise-induced hearing loss (NIHL) is one of the most important problems affecting both social and professional life of patients. There is no treatment method considered to be successful on the hearing loss that has become a permanent nature. Aim of this study is to evaluate protective effect of Korean Red Ginseng (KRG) against NIHL in an animal model. Methods: Twenty-eight rats were separated into four groups [control saline (group I), control KRG (group II),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
(54 reference statements)
0
5
0
Order By: Relevance
“…Recent studies have highlighted the potential of ginsenosides to protect against hearing loss [ 19 , 20 ]. However, the effects of ginsenosides, G-Rc in particular, on cellular homeostasis and on the response to pro-inflammatory stimuli remain to be determined.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have highlighted the potential of ginsenosides to protect against hearing loss [ 19 , 20 ]. However, the effects of ginsenosides, G-Rc in particular, on cellular homeostasis and on the response to pro-inflammatory stimuli remain to be determined.…”
Section: Resultsmentioning
confidence: 99%
“…Ginsenosides exhibit protective effects against ischemia-induced damage to the spiral ganglion cells and reduce noise-induced apoptotic cell death in the organ of Corti and spiral ganglion [ 20 ]. However, the effects of G-Rc on cochlear hair cell differentiation remain elusive.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When rats were supplemented with Korean red ginseng (KRG) for one week prior and during exposure to gentamicin, researchers observed a significant improvement in hearing thresholds and reduction in cochlear hair cell damage [214]. In rats exposed to prolonged high-decibel noise, supplementation with KRG protected against cell death in both the organ of Corti and spiral ganglion [215]. In an effort to understand the effects of isolated ginsenosides, Fujita and colleagues demonstrated ginsenoside-Rb1 reduces the loss of spiral ganglion cells after the induction of cochlear ischemia by occlusion [216].…”
Section: Epigallocatechin Gallate (Egcg)mentioning
confidence: 99%
“…Korean red ginseng (Araliaceae; Panax ginseng C.A.Mey) has been used in folklore medicine for 2000 years and is currently being investigated for a variety of conditions including metabolic syndrome ( Aminifard et al, 2021 ), inflammatory bowel disease ( Kang et al, 2021 ) and diabetes ( Liu et al, 2021 ). Studies have shown that Korean red ginseng has otoprotective activities including alleviation of cisplatin-induced ototoxicity in vitro and in vivo ( Im et al, 2010 ), attenuation of noise-induced hearing loss ( Mungan Durankaya et al, 2021 ) and amelioration of cochlear damage ( Tian et al, 2013 ) and vestibular dysfunction ( Tian et al, 2014 ). In an open-label RCT, patients with chronic tinnitus received Korean red ginseng 1,500 mg/day or 3,000 mg/day, or G. biloba extract 160 mg/day for 4 weeks.…”
Section: Other Herbal Medicines For the Treatment Of Tinnitusmentioning
confidence: 99%